Two Views of American Slavery: The Character of Jim in Mark Twain's Novel Adventures of Huckleberry Finn and the Character of Kunta Kinte in Alex Haley's Novel Roots - Židek, Petr (Univerzita Pardubice, 2008)
The thesis deals with the US slavery and how it is reflected in literary works. It also deals with methods applied by Mark Twain in Adventures of Huckleberry Finn and by Alex Haley in Roots to portray their respective characters, Jim and Kunta Kinte.
Dva pohledy na americké otroctví: postava Jima v románu Marka Twaina Dobrodružství Huckleberryho Finna a postava Kunty Kinte v románu Alexe Haleyho Kořeny
Keywords: otroctví; porovnání; slavery; Mark Twain; Alex Haley; Kunta Kinte; comparison